Application Comparison of the Lex Loci Delicti Commission Theory between the Oil Spill Case in the Gulf of Mexico and the Carbon Emissions Case in the Netherlands - Christopher, Anderson (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The event of a disastrous oil spill from British Petroleum's offshore drilling installation on the 20th of April 2010 was caused by a leaking underwater pipeline, which polluted the waters of the Gulf of Mexico. Subsequently, there was the Carbon Emission Case in the Netherlands, which required Shell to reduce their carbon emissions by 45% by 2030 from the carbon emissions generated in 2019. Both events were deeply concerning and directly effected the citizens of the respective countries. In the first case, the spill of approximately 5,000 barrels or 210,000 gallons (795,000 liters) of crude oil spread extensively due to ocean currents where the contaminated area ended up covering 9,933 square kilometers of ocean (77 x 129km). This oil spill, which was a result of British Petroleum's negligence, lead to legal action taken against the company for violations of international environmental laws, due to environmental pollution. In the second case, Shell, was deemed to have contributed significantly to climate change in the Netherlands. The company was responsible for twice the amount of greenhouse gas emissions than the Netherlands. The research method employed in this journal uses a normative juridical research approach, focusing on legal norms within the decisions for Case MDL No. 2179 and the Verdict issued by the Haugue District Court. In this journal, the author concludes that both British Petroleum and Shell have been proven to commit unlawful acts against the international environment laws through environmental pollution.